Inovasi Diversifikasi Pangan Lokal melalui Pemanfaatan Daun Singkong menjadi Keripik sebagai Upaya Pengurangan Limbah dan Peningkatan Pendapatan Masyarakat - Pamujiati, Agustia Dwi; Artini, Widi; Andajani, Wiwiek; Widiyono, Wahyu; Mulyadi, Mochtar Nova (Kadiri University, 2025)
Community service aims to increase the utilization of cassava leaves as a value-added food ingredient by innovating cassava leaf chips (Daun Crips) in Jombok Village, Pule District, Trenggalek Regency, East Java. Cassava leaves, which have traditionally been considered agricultural waste, have a high protein content and significant economic potential if processed properly. The implementation method was carried out through a participatory approach that involves the community in counseling, technical training in production, packaging, branding, and product economic analysis. Evaluation of activities using pre-tests and post-tests on six assessment aspects revealed an increase in the average score from 57.2 to 86.8, representing a 51.8% improvement. The highest increases were observed in technical processing skills (63.6%) and production cost analysis (57.7%). The resulting product has characteristics of being crispy, savory, and having a low water content (3.8%), in accordance with snack food quality standards. This activity has a positive impact by increasing the knowledge, skills, and entrepreneurial motivation of the community, as well as encouraging the formation of Joint Business Groups as the foundation for productive economic businesses based on local potential. This program is a real-world example of the implementation of local food diversification, which can reduce agricultural waste, increase community income, and support sustainable village economic development. Pengabdian kepada masyarakat memiliki tujuan meningkatkan pemanfaatan daun singkong sebagai bahan pangan bernilai tambah melalui inovasi produk keripik daun singkong (Daun Crips) di Desa Jombok, Kecamatan Pule, Kabupaten Trenggalek, Jawa Timur. Daun singkong yang selama ini dianggap limbah pertanian memiliki kandungan protein tinggi dan potensi ekonomi yang besar apabila diolah secara tepat. Metode pelaksanaan dilakukan melalui pendekatan partisipatif yang melibatkan masyarakat dalam penyuluhan, pelatihan teknis produksi, pengemasan, branding, serta analisis ekonomi produk. Evaluasi kegiatan dengan menerapkan pre-test dan post-test pada enam aspek penilaian menunjukkan adanya peningkatan rata-rata skor dari 57,2 menjadi 86,8 atau meningkat sebesar 51,8%, dengan peningkatan tertinggi pada keterampilan teknis pengolahan (63,6%) dan analisis biaya produksi (57,7%). Produk yang dihasilkan memiliki karakteristik renyah, gurih, serta kadar air rendah (3,8%), sesuai dengan standar mutu pangan ringan. Kegiatan ini memiliki efek positif dengan meningkatnya pengetahuan, keterampilan, dan motivasi kewirausahaan masyarakat, serta mendorong terbentuknya Kelompok Usaha Bersama sebagai embrio usaha ekonomi produktif berbasis potensi lokal. Program ini menjadi contoh nyata penerapan diversifikasi pangan lokal yang mampu mengurangi limbah pertanian, meningkatkan pendapatan masyarakat, dan mendukung pembangunan ekonomi desa berkelanjutan.